2023
DOI: 10.3390/app13179907
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Oral Maxillofacial Surgery: A Comprehensive Review on 3D Printing and Virtual Surgical Planning

Jwa-Young Kim,
Yong-Chan Lee,
Seong-Gon Kim
et al.

Abstract: This comprehensive review explores the advancements in Orthognathic and Oral Maxillofacial Surgery, focusing on the integration of 3D Printing and Virtual Surgical Planning (VSP). Traditional surgical methods, while effective, come with inherent risks and complications, and can lead to variability in outcomes due to the reliance on the surgeon’s skill and experience. The shift towards patient-centric care necessitates personalized surgical methods, which can be achieved through advanced technology. The amalgam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…VSP has the potential to improve the surgeon's understanding of the individual anatomy of the patient, as well as to provide a computer-driven workflow for jaw reshaping, thus replacing the traditional 2D methodologies used in orthodontic surgery. Furthermore, studies have demonstrated that 3D-planned treatment regimens can improve precision and improve results [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…VSP has the potential to improve the surgeon's understanding of the individual anatomy of the patient, as well as to provide a computer-driven workflow for jaw reshaping, thus replacing the traditional 2D methodologies used in orthodontic surgery. Furthermore, studies have demonstrated that 3D-planned treatment regimens can improve precision and improve results [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…By offering high levels of accuracy, time efficiency, and adaptability, VSP stands as a revolutionary tool in the realm of orthognathic surgery [ 9 , 12 ]. Its growing adoption is a testament to its effectiveness and the tangible benefits it offers to both surgeons and patients alike [ 10 , 20 ].…”
Section: Main Textmentioning
confidence: 99%
“…3D printing, also known as additive manufacturing, is a technology that allows for the creation of three-dimensional objects from digital models [ 21 ]. In the realm of orthognathic surgery, 3D printing has found a variety of applications, including the fabrication of surgical guides, anatomical models for preoperative planning, and even custom implants [ 10 ]. These applications enhance the precision and predictability of surgical outcomes, thereby elevating the standard of care (Fig.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations